Challenges in the use of the mental health information system in a resource-limited setting: lessons from Ghana - Lily Kpobi; Leslie Swartz; Angela L. Ofori-Atta (BMC, 2018)
Abstract Background One of the most successful modes of record-keeping and data collection is the use of health management information systems, where patient information and management plans are uniformly entered into a database to streamline the information and for ease of further patient management. For mental healthcare, a Mental Health Information System (MHIS) has been found most successful since a properly established and operational MHIS is helpful for developing equitable and appropriate mental health care systems. Until 2010, the system of keeping patient records and information in the Accra Psychiatric Hospital of Ghana was old and outdated. In light of this and other factors, a complete reforming of the mental health information systems in three psychiatric hospitals in Ghana was undertaken in 2010. Four years after its implementation, we explored user experiences with the new system, and report here the challenges that were identified with use of the new MHIS. Methods Individual semi-structured interviews were conducted with nine clinical and administrative staff of the Accra Psychiatric Hospital to examine their experiences with the new MHIS. Participants in the study were in three categories: clinical staff, administrator, and records clerk. Participants' knowledge of the system and its use, as well as the challenges they had experienced in its use were explored using an interpretative phenomenological approach. Results The data suggest that optimal use of the current MHIS had faced significant implementation challenges in a number of areas. Central challenges reported by users included increased workload, poor staff involvement and training, and absence of logistic support to keep the system running. Conclusions Setting up a new system does not guarantee its success. As important as it is to have a mental health information system, its usefulness is largely dependent on proper implementation and maintenance. Further, the system can facilitate policy transformation only when the place of mental health in district, regional and national health discourse improves.